Is the sex communication of two pyralid moths, Plodia interpunctella and Ephestia kuehniella, under circadian clock regulation? - Závodská, Radka; Fexová, Silvie; von Wowern, Germund; Han, Gui-Biao; Dolezel, David; Sauman, Ivo (Journal of biological rhythms, 2012)
Females of the Indian meal moth, Plodia interpunctella, and females of the Mediterranean flour month, Ephestia kuehniella (both Lepidoptera: Pyralidae), exhibit daily rhythms in calling behavior. The peak in P. interpunctella calling occurs at dusk, whereas E. kuehniella calls preferentially at dawn. This behavior turned arrhythmic in P. interpunctella females in constant darkness (DD) and remained arrhythmic in constant light (LL), whereas E. kuehniella females showed a persistent rhythm in DD and suppression of the behavior in LL, indicating regulation by a circadian clock mechanism. The rhythm of male locomotor activity corresponded well with the sexual activity of females, reaching the peak at dusk in P. interpunctella and at dawn in E. kuehniella. An immunohistochemical study of the pheromone biosynthesis activating neuropeptide, corazonin, and pigment dispersing factor revealed distinct sets of neurons in the brain-subesophageal complex and in the neurohemal organs of the 2 species.
Keywords: Animals; můry; biologické modely; Female; ženské pohlaví; sexuální lákadla; druhová specificita; Immunohistochemistry; Hormones; Models, Biological; pigmentace; Circadian Rhythm; Moths; Species Specificity; imunohistochemie; cirkadiánní rytmus; Pigmentation; Animal Communication; Light; Sex Factors; Male; hmyz; sexuální faktory; Neuropeptides; komunikace zvířat; neuropeptidy; Pheromones; hormony; zvířata; světlo; mužské pohlaví; sexuální chování zvířat; feromony; Sexual Behavior, Animal; Insecta; Sex Attractants